2020
DOI: 10.21873/invivo.11909
|View full text |Cite
|
Sign up to set email alerts
|

Self-expandable Metal Stent as a Bridge to Surgery for Colorectal Cancer: Safety and Oncological Outcomes

Abstract: Background/Aim: Self-expandable metal stent (SEMS) as a bridge to surgery (BTS) for obstructive colorectal cancer (CRC) raises concerns regarding the short-term as well as oncological outcome. The present study aimed to investigate the safety of SEMS placement and risk factors of worse short-term and oncological outcomes as BTS. Patients and Methods: Twenty-four patients with obstructive CRC who underwent SEMS placement as BTS were included. Success rate of SEMS placement and 2-year relapse-free survival (RFS)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 23 publications
2
6
0
Order By: Relevance
“…The utility of colonic stenting has mainly been evaluated on the basis of the surgical outcomes, including long‐term survival and postoperative complications, of Japanese patients who were bridged for curative surgery 2–6,9 . The present study suggests that colonic stenting for decompression for obstructive colorectal cancer is as valuable and effective in patients who undergo systemic chemotherapy and palliative therapy as it is in patients who are bridged for curative surgery, which are partly supported by the findings of previous studies 7,12 …”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“…The utility of colonic stenting has mainly been evaluated on the basis of the surgical outcomes, including long‐term survival and postoperative complications, of Japanese patients who were bridged for curative surgery 2–6,9 . The present study suggests that colonic stenting for decompression for obstructive colorectal cancer is as valuable and effective in patients who undergo systemic chemotherapy and palliative therapy as it is in patients who are bridged for curative surgery, which are partly supported by the findings of previous studies 7,12 …”
Section: Discussionsupporting
confidence: 83%
“…7,12 Previous studies have demonstrated the safety of colonic stent insertion and have identified the risk factors for stenting in patients who received curative surgery, which include tumor length and staging, the stenosis site of colorectal cancer, the interval to the surgery, and the general condition of the patient, including nutrition status. 6,8,10,16 The present study indicates that colonic stenting for patients who received chemotherapy and palliative therapy was performed safely without serious early complications compared with that for patients who received curative surgery, regardless of risk status for tumor length and staging, stenosis site, survival prognosis, and general condition.…”
Section: Discussionmentioning
confidence: 61%
See 2 more Smart Citations
“…Interestingly, although colon or rectal SEMS positioning might be risky because of the eventual serious complications, including perforation, we only recorded some minor complications (3,5). We recommend stent positioning to be performed by experienced staff personnel with a proper preoperative preparation (nasogastric tube and fasting with correction of the fluid and electrolytes imbalance with the intent to reduce the caliber mismatch from above and below the tumor stricture) and selection of the patients amenable of this procedure excluding patients with residual gross colonic dilatation, in whom there is a persistent significant risk of perforation and/or ischemia, and can undergo conventional surgery (3,5,13,(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29).…”
Section: Discussionmentioning
confidence: 99%